Congregational Political Activity and Same‐Sex Marriage: Social Movement Theory and Evidence for Contextual Influence. Issue 3 (6th June 2014) - Adler, Gary; Hoegeman, Catherine; West, A. Joseph
<x xml:space="preserve">Abstract</x> We interpret three strands of social movement theory (social threat, opportunity structure, and resource mobilization) to understand religious congregations' political activity related to same‐sex marriage. Using a unique, national data set from the 2008 presidential election, we show the importance of the anti‐same‐sex marriage discursive opportunity structure (DOS) for facilitating, and occasionally constraining, congregational political activity. Other theoretical factors influence congregations under limited, although important, conditions. Our research develops a nuanced understanding of congregations' roles in social movements that prioritize institutionalized political activity and expands DOS theory in relation to local religious organizations.